(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Guillain-Barre Syndrome (GBS) is an acute, frequently severe and fulminant polyradiculopathy that is autoimmune in nature and that causes acute neuromascular failure. The condition is quite common in Bangladesh. GBS is an autoimmune and post-infectious immune disease. Objectives: To see the different presentation and outcome of GBS in combined military hospital (CMH) Dhaka. Materials and Methods: This was a retrospective observational study conducted on all the GBS patients admitted in the Neurology Ward of CMH Dhaka from January 2005 to July 2010. Total 25 patients clinical and laboratory data including CSF analysis, electrophysiological study data were collected from patients’ case sheet. Results: Among the 25 GBS patients male was 22 (88%) and female 03(12%) and most common age group affected was 31-40 years comprising of 09(36%) patients. The most common types of GBS patients were acute inflammatory demyelinating polyneuropathy (AIDP) 17(68%) patients and 10(40%) patients were found to have history of upper respiratory tract infection (URTI). Albuminocytological dissociation was found in 20(80%) patients in CSF study. Intravenous immunoglobulin therapy was given to 13(52%) patients, of them 09(36%) patient needed mechanical ventilation; rest 12(48%) patients were treated conservatively. The final outcome was full recovery 22(88%) patients, 02(8%) patients had residual disability and only one patient died after 2 years of GBS. Conclusion: GBS is an important cause of peripheral neuropathy. Patient should be monitored carefully because a significant number of patients ultimately require mechanical ventilation for respiratory failure which may be of sudden onset. JAFMC Bangladesh. Vol 16, No 2 (December) 2020: 44-46